PERANAN LOYALITAS DALAM MEMEDIASI TRUST DAN EXPERENSIAL MARKETING TERHADAP MINAT BELI ULANG KOPI ABC DI DESA BATTAL KECAMATAN PANJI KABUPATEN SITUBONDO - Oktavia, Mita; Tulhusnah, Lusiana; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2023)
The increasingly sophisticated world of technology makes the development of information and communication in the current era of globalization develop very rapidly, this is supported by people who are very dependent on technology in their daily activities. The purpose of this study is to examine the role of loyalty in mediating trust and experiential marketing on the interest in repurchasing ABC Coffee in Battal Village, Panji District, Situbondo Regency. The population in this research is Koipi ABC consumers. The sampling technique is determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that Trust has a significant positive effect on Loyalty, Experiential marketing has a significant negative but not significant effect on Loyalty, Trust has a significant positive effect on Repurchase Intention. Experiential marketing has a negative but not significant effect on repurchase intention. Loyalty has a significant positive effect on repurchase intention. Trust on repurchase intention through loyalty has a significant positive effect, experiential marketing on repurchase intention through loyalty has a positive effect.